A Study on Customers’ Preference towards Online Food Orders with Reference to South Chennai - Eswaran, B. (International Journal of Psychosocial Rehabilitation, 2020)
Online food ordering is a process of ordering the food through mobile app or restaurant’s website or multi-restaurant’s mobile app or website. It comprises the customer chooses the restaurants in his choice, going through the menu items, choose a food item, and finally choosing delivery or pick up. This study This study deals with the customer’s preferences towards ordering food items online in south Chennai. Descriptive research method was used in this study. The survey tool used here was questionnaire. The primary data was collected through simple random sampling for infinite population. 250 samples were collected. People who were using the online food delivery app in south Chennai were given questionnaire to respond. This study concludes that occupation of the respondents had a considerable impact on type of food items and time of food items ordered. The mobile online food ordering and delivery apps were used to order foods selectively for the different time of orders placed.